Qualidade microbiológica de água tratada para hemodiálise e caracterização de bactérias patogênicas - Souza, Bárbarah Gregório de Araújo (2015)
Hemodialysis is a primary treatment for chronic renal patients in the terminal phase. In this therapy, the water is used for the dialysis solution production and dialyzers reuse, and therefore the microbiological quality should be guaranteed, once excessive levels of bacteria are responsible for symptoms such as fever, chills, hypotension and shock, and may even lead to death of patients. Thus, this study aimed to evaluate the water microbiological quality used in hemodialysis centers and characterize isolated pathogenic bacteria from this water. During the months of May and June 2014, were collected in two stages, water samples from four collection points in 12 hemodialysis centers of the cities of Goiania-GO and Aparecida de Goiânia-GO. The protocol followed the microbiological parameters of Board Resolution No. 11/2014, in addition to fecal coliforms, Escherichia coli and Pseudomonas aeruginosa research, according to the American Public Health Association. The strains of pathogenic bacteria were characterized phenotypic and genotypically through the antibiogram and Pulsed Field Gel Electrophoresis. Of the 96 water samples, 7.3% were classified contaminated with total coliforms, 1.1% by fecal coliforms, 18.7% by heterotrophic bacteria and 10.4% by P. aeruginosa, the latter being present in 6 hemodialysis centers. E. coli strains were not isolated in the water samples studied. All P. aeruginosa strains were resistant to cefepime and only one strain was also resistant to aztreonam and piperacillin-tazobactam. Genotypic analysis revealed eight different electrophoretic profiles and showed the persistence of the same bacteria clones in the two phases of collection in a hemodialysis center. It can be concluded that the water used in dialysis units has unsatisfactory hygienic and sanitary conditions and pathogenic bacteria strains have antibiotic resistance pattern used in your control and high genetic diversity, revealing the potential health risk to patients undergoing hemodialysis.